Lifestyle and dietary habits of patients with gout followed in rheumatology settings - M. Manara; G. Carrara; C. A. Scirè; M. A. Cimmino; M. Govoni; C. Montecucco; M. Matucci-Cerinic; G. Minisola; the KING study group (PAGEPress Publications, 2016)
Diet and lifestyles modification are core aspects of the non-pharmacological management of gout, but a poor consistency with suggested guidelines is reported. This study aimed to investigate dietary and lifestyle habits of patients with gout followed in rheumatology settings. Data were retrieved from the baseline dataset of the KING study, a multicentre cohort study of patients with gout followed in rheumatology settings. Dietary habits were assessed with the Italian National Institute of Statistics (ISTAT) food-frequency questionnaire and compared with reported data about general population. The relative increase of exposure was estimated by standardized prevalence ratios adjusted for gender, age and geographical distribution. The study population included 446 patients, with a mean age of 63.9 years and a M/F ratio of 9:1. Compared to the Italian population, gouty patients showed a higher prevalence of obesity [1.82 (1.52-2.18)] and a higher consumption of wine [1.85 (1.48-2.32)] and beer [2.21 (1.68-2.90)], but a lower prevalence of smoking and a lower intake of liquor. They showed a lower intake of red meat [0.80 (0.71-0.91)], but a similar intake of other tested dietary factors. Gouty patients' lifestyle is still partially different from the recommended.